Practices of cultural democracy : the Cultura Viva program in Brazil - Moreira, João Fernandes da Luz (2022)
Despite the socio-economic crisis Brazil has experienced since 2014 and that has been considerably deepened by political instability in a polarized scenario, in 2022 the cultural area resists. The sector has confronted a deliberate dismantlement in the last two governments, Michel Temer's (2016-2018) and, since 2019, Jair Bolsonaro’s. On the other hand, Luiz Inácio Lula da Silva’s mandates (2003-2010) represented in Brazilian contemporary history a radical paradigmatic shift to the approach to culture from a political and ideological perspective, as culture was a crucial aspect for fostering social equality and economic development, besides its role for overcoming social exclusion. In other words, culture was transformed into one of the main pillars of Brazilian identity's construction and preservation (Lula da Silva 2003). Twelve years after the end of Lula's government, this research examines practices of cultural democracy during his two mandates through the analysis of the National Plan of Culture and of the National System of Culture. Special attention is given to the Cultura Viva program and its pontos de cultura, understood as the most significant governmental initiative to expand and democratize the access to culture, especially in terms of its production. Bearing in mind the political disruption and the dismantlement of the cultural-artistic sector in the last two governments, this dissertation aims at evaluating Lula’s practices of cultural democracy and the legacy of Cultura Viva.